Knowledge, Practice, and Attitude on Food Handling of Street Food Vendors in Biliran Province - Paul Hector E. Gonzales; Reymark S. Pabilando (International Journal Labs, 2023)
This study aimed to investigate the knowledge, practice and attitude of street food vendors in Biliran Province, Philippines, towards food handling. Street food vending is a major source of livelihood for many Filipinos, but it is also a source of health risks due to improper food handling. The study aimed to identify the factors that influence the food handling practices of street food vendors in Biliran Province. A descriptive cross-sectional survey was conducted among street food vendors in Biliran Province. A structured questionnaire was used to collect data on street food vendors' knowledge, practice and attitude towards food handling. Descriptive statistics were used to analyze the data. The results showed that most of the street food vendors in Biliran Province had inadequate knowledge and practice regarding food handling. Most respondents had a positive attitude towards food handling but lacked adequate information on the proper food handling practices. The results of this study suggest that street food vendors in Biliran Province need to be provided with adequate information and training on food handling to improve their knowledge and practice. The local government should also consider implementing health and safety regulations to ensure street food safety.